Cambridge Preliminary English Test 4 with answers - Cambridge University (Fahasa, 2014)
Authentic examination papers from cambridge esol; Official preparation material for cambridge english: preliminary, also known as preliminary english test (Pet); The Cambridge Preliminary English Test 4 practice tests provide candidates with an excellent opportunity to familiarise themselves with the 2004 PET exam and to practise examination techniques. The Student's Book contains practice material for Paper 1 (Reading and Writing) and Paper 2 (Listening), along with attractive colour visual material for Paper 3 (Speaking), enabling students to prepare thoroughly for the paired Speaking test. The 'with answers' edition contains a comprehensive section of keys and tapescripts, making it ideal for self-study. The Audio CD Set contains the listening material for Paper 2 in the same timed format as the exam itself